A Study on Quantified Impacts of Construction Labour Productivity Towards Project Performance - Kavithra, S. S.; Ambika, D.; Shankari, R. Shreena (International Journal of Scientific Research in Civil Engineering, 2016)
The construction sector plays a vital role in all developing countries. The main factors that affects the construction growth is labour productivity and its performance. The main and precious resources of construction are labours. This research mainly deals with the study on construction labours, identifying the critical factors influencing labours and suggestions to overcome the same. Several research papers have been collected and reviewed. The Factors affecting labour productivity in construction industries are collected from both literature review and direct inspection. The questionnaire survey was conducted among various labours in construction projects. Then the collected data are analyzed using statistical package for the social science (SPSS) and the appropriate solutions are given for all impacts.
Keywords: Labour productivity; Critical factors; Labour productivityCritical factors; Construction sector; Data collection and Analysis